Association of provider HPV vaccination training with provider assessment of HPV vaccination status and recommendation of HPV vaccination. Issue 6 (30th November 2022) - Osaghae, Ikponmwosa; Darkoh, Charles; Chido-Amajuoyi, Onyema Greg; Chan, Wenyaw; Wermuth, Paige Padgett; Pande, Mala; Cunningham, Sonia a; Shete, Sanjay
ABSTRACT: The delivery of strong HPV vaccine recommendations hinges on the expertise of healthcare providers (HCPs) in assessing patients' status and recommending HPV vaccination. We conducted a population-based cross-sectional study of HCPs practicing in Texas to examine the relationship between HPV vaccination training of HCPs and HPV vaccination status assessment and recommendation. Logistic regression analyses were used to assess the association between HCPs' formal training and recency of training in HPV vaccination promotion or counseling with HPV vaccination status assessment and recommendation. Of the 1, 283 HCPs who completed the online survey, 43% had received training in HPV vaccination promotion or counseling, 47% often/always assess HPV vaccination status, and 59% often/always recommend HPV vaccination. Compared with HCPs who received no training, those who received training had over four times higher odds (adjusted odds ratio [AOR]: 4.32; 95% CI: 3.06–6.10) of often/always assessing HPV vaccination status and over three and half times higher odds (AOR: 3.66; 95% CI: 2.73–4.90) of often/always recommending HPV vaccination. Furthermore, HCPs who recently received HPV vaccination training had higher odds of HPV vaccination status assessment and recommendations than those without training. Hispanic HCPs had higher odds of often/always assessing HPV vaccination status and recommending vaccination than did non-Hispanic White HCPs. Also, nurses and physician assistants had lower odds of often/always assessing HPV vaccination status and recommending HPV vaccination than did physicians. Targeted and continuous training of HCPs in HPV vaccination promotion or counseling is needed to increase HPV vaccination status assessment, recommendation, and uptake rates.